Time-dependent haemoperfusion after acute paraquat poisoning - Hao-Ru Wang (Scientific Reports, 2017)
Abstract Early haemoperfusion (HP) therapy has been found to be very effective in acute paraquat (PQ) poisoning, but the effective rescue window is still uncertain. Demographic data and the type of therapies administered of 621 patients were included as confounding factors in this retrospective study. After receiver operating characteristic curve analysis and intra-group/subgroup analysis, the initiation of glucocorticoid therapy within 3 hrs of exposure with a second treatment given <21 hrs after exposure, HP initiated within 4 hrs of exposure with a second treatment given <20 hrs after exposure, the appearance of pulmonary lesions ≤8 days after exposure and six other variables were used in a multiple analysis. The strength of positivity of the PQ urine test on admission, HP initiated within 4 hrs of exposure with a second treatment given <20 hrs after exposure, the appearance of pulmonary lesions ≤8 days after exposure, and stage III AKI on admission were independent factors of survival probability. HP therapy for acute PQ poisoning was the main therapeutic intervention investigated in this study. Outcomes were time dependent, and the crucial factor was the initiation of therapy within 4 hrs of PQ poisoning followed by a second treatment within 20 hrs.